L2 Spanish apologies development during short-term study abroad - Hernández, Todd A. (Studies in Second Language Learning and Teaching, 2018)
The present study examined the apologies of 18 study abroad (SA) students during a short-term SA experience in Madrid, Spain. Apologies were assessed with a discourse completion task (DCT) consisting of five vignettes that varied across three variables: relative social status of the interlocutor, relative social distance, and seriousness of the offense. Based on performance ratings assigned to them by two native Spanish speakers, the students made significant gains in pragmatic appropriateness from pretest to posttest, on two out of the five individual vignettes, and on the five combined vignettes. Examination of the students’ apologies before and after SA further revealed that they increased several strategies during their time abroad. Despite these gains, other aspects of the SA group’s performance remained the same or, in some cases, moved in the opposite direction of the target norm. Moreover, the students also demonstrated continued overreliance on routine, formulaic expressions on the posttest DCT while underusing some important target-like mitigation strategies. Given the study’s findings, the researcher offers recommendations for teaching pragmatics before and during the SA experience.